Relationship of field and in vitro fertility of dairy bulls with sperm parameters, including DAG1 and SERPINA5 proteins - Zoca, Saulo Menegatti; Walker, Julie A.; Kline, Adalaide C.; Andrews, Taylor N.; Rich, Jerica J. J.; Epperson, Kaitlin M.; Drum, Jessica Nora; Ortega, M. Sofia; Cushman, Robert A.; Perry, George A. (Frontiers in Animal Science, 2023)
Introduction Sperm interacts with the female reproductive tract and oocyte through proteins, and these cell-to-cell interactions may play a role in sperm fertility. For consideration of a protein as a potential marker of fertility, there must be variability expressed among animals. The proteins dystroglycan (DAG1) and plasma serine protease inhibitor (SERPINA5) have been reported to play a role in cell-to-cell interactions. Thus, the objectives of this study were to characterize the localization and abundance variability of DAG1 and SERPINA5 in bovine sperm, and to investigate the relationship of DAG1 and SERPINA5 with field fertility (i.e., sire conception rate; SCR), in vitro embryo production (IVP), and sperm parameters. Material and methods Dairy bulls (n = 22) were classified as high-SCR (SCR > 1.0) or low-SCR (SCR < –4.0), and good [blastocyst (BL)-by-cleavage (CL) ratio (BL/CL) > 39%] or poor (BL/CL < 38%) BL/CL. Sperm was evaluated for DAG1 and SERPINA5 immunolocalization, and concentration in two separate ejaculates. Variance between bulls compared with within bulls was evaluated using a generalized linear model (GLM) procedure. The relationship of SCR and IVP classification on DAG1 and SERPINA5 concentrations, percentage of tail labeled for SERPINA5, SCR, sperm total and progressive motility, sperm plasma membrane integrity (PMI), CL, BL, and BL/CL were evaluated with the GLIMMIX procedure, and the correlations between these variables were evaluated. Results Both proteins were localized on the sperm head; however, SERPINA5 was also localized on the sperm tail. There was greater variance in concentration among bulls than within bulls for DAG1 (P < 0.0001; 69.4 vs. 49.1, respectively) and SERPINA5 (P < 0.0001; 325.8 vs. 285.4, respectively). There was a positive correlation between the concentrations of DAG1 and of SERPINA5 (P = 0.01; r = 0.54). In addition, the percentage of tail labeled for SERPINA5 was correlated with PMI (P = 0.05; r = 0.44). There was no relationship between SCR and IVP classifications and DAG1 (P ≥ 0.55), SERPINA5 (P ≥ 0.54), or the percentage of sperm tail labeled for SERPINA5 (P ≥ 0.22). Discussion In conclusion, DAG1 and SERPINA5 were localized to the sperm head, and SERPINA 5 was also localized to the tail. Concentrations of DAG1 and SERPINA5 on the sperm head were correlated with each other. The percentage of tail labeled for SERPINA5 was correlated with sperm PMI; however, neither protein was associated with SCR or IVP. Thus, when evaluated by immunofluorescent microscopy, DAG1 and SERPINA5 concentrations are variable and are not good fertility markers for bull sperm.